PERFORMANCE OF THE AGRICULTURAL AND NON-AGRICULTURAL SECTORS IN THE ECONOMY OF PONOROGO DISTRICT - Laila Annisa Putri; Sri Widayanti; Mirza Andrian Syah (RADJA PUBLIKA, 2024)
Economic growth is an indicator for assessing economic conditions in a region which can be seen through the economic conditions of a region through the condition of the economic sectors in that area. This research aims to analyze the performance of the agricultural and non-agricultural sectors by knowing the position of the agricultural sector and non-agricultural sector in Ponorogo Regency by determining the current and future position of the agricultural and non-agricultural sectors and identifying factors that cause changes in the performance of the agricultural and non-agricultural sectors. . Data collection in this research used secondary data obtained from the Central Statistics Agency. The analytical method used in this research uses the Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Shift Share methods. From the LQ calculation, the agricultural sector is the base sector with an LQ value of 2.48. From the DLQ analysis, the agricultural sector experienced a change in performance to become a non-base sector or cannot be expected to become a basis in the future with a DLQ value of 0.261. The factor that causes changes in the performance of the non-agricultural sector is the economic structure factor with an SSS value greater than the LSS value.